27 Gb/s PRBS Generator with In-Operation Programmable Taps for PMCW Radar - Probst, Florian; Engelmann, Andre; Weigel, Robert (2024 IEEE 24th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2024)

A 15-Gb/s PMCW Radar PRBS-Generator for MIMO and Joint Radar-Communication Systems - Probst, Florian; Engelmann, Andre; Hetterle, Philip; Issakov, Vadim; Weigel, Robert; Dietz, Marco (2022 Asia-Pacific Microwave Conference, 2022)
This paper presents an integrated baseband pseudo-random noise generator at 15 Gb/s for phase-modulated continuous-wave (PMCW) radar systems. Through slow-time modulating an outer code (OC) onto a pseudo-random binary sequence (PRBS), the circuit enables MIMO and joint radar-communication (RadCom) systems in the D-Band and above. To the best of the authors’ knowledge, this has not yet been demonstrated. The mixed-signal circuit consumes 7.2mW in power and 400 × 530μm2 in area. It was realized in a 22nm fully-depleted silicon on insulator (FDSOI) technology, where the PRBS is generated by a shift register formed by true single-phaseclock (TSPC) flip-flops.<br
Keywords: MIMO radar; phase-modulated continuouswave (PMCW); radar-communication (RadCom); true singlephase-clock (TSPC).

A 1.7 dBm OP1dB D-Band Up-Conversion Mixer Utilizing Adaptive Back-Gate Bias in 22 nm FDSOI - Huang, Tianzhu; Hetterle, Philip; Engelmann, Andre; Probst, Florian; Schrotz, Albert-Marcel; Weigel, Robert; Fischer, Georg (2024 Asia-Pacific Microwave Conference, 2024)

A 200 GHz Area-Efficient 4-stage Power Amplifier with Stacked Output Stage in 22 nm FDSOI - Scheller, Kai; Engelmann, Andre; Probst, Florian; Flohr, Michael; Weigel, Robert; Schrotz, Albert-Marcel; Fischer, Georg (2024 Asia-Pacific Microwave Conference, 2024)
This paper presents a compact, low DC-power four-stage G-Band power amplifier (PA) integrated into a 22 nm fully-depleted silicon-on-insulator (FDSOI) technology. The three common-source driver stages and the output stage utilize the capacitive neutralization technique for gain-boosting. The output stage is implemented as a tuned stacked-FET amplifier for further gain and output power enhancement. Low-loss stacked transformers are employed as matching networks to achieve a small core-area footprint of 0.024 mm2. The PA attains a gain of 12.5 dB, a 1 dB output compression point OP1dB of -4 dBm, and an extrapolated saturated output power Psat of 3.7 dB at 200 GHz, based on simulation and measurement. Supplied by 1.6 and 0.85 V, the circuit´s DC-power consumption is below 57 mW.<br
Keywords: CMOS; FDSOI; G-Band; millimeter-wave; power amplifier (PA); stacked FETs

A 21 Gb/s Arbitrary Binary Sequence Generator for PMCW Radar based on a TSPC Serializer in 22 nm FDSOI - Probst, Florian; Engelmann, Andre; Issakov, Vadim; Weigel, Robert (IEEE MTT-S International Microwave Symposium Digest, 2023)
This work presents an arbitrarily programmable pseudo-random binary sequence (PRBS) generator for phase-modulated continuous-wave (PMCW) radar transmitters. It incorporates a mixed-signal architecture with a digitally implemented shift register connected to a novel serializer architecture based on true single-phase-clock (TSPC) flip-flops. Unlike static, non-configurable linear-feedback shift registers (LFSRs), this circuit can generate more complex sequences, like the almost perfect auto-correlation sequence (APAS), that exhibit a better radar performance. The circuit is realized on a 22nm fully-depleted silicon on insulator (FDSOI) technology and consumes a total chip area of 600×530µm2. On-wafer measurements show a maximum chip rate of 21Gb/s at a 16.9mW power consumption. To the best of the authors' knowledge, the proposed circuit marks the first programmable PRBS generator operating at this high chip rate. It paves the way for on-chip generation of complex broadband sequences for millimeter-wave digital MIMO radar systems for consumer or automotive applications.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Almost perfect auto-correlation sequences (APAS); fully-depleted silicon on insulator (FDSOI); phase-modulated continuous-wave (PMCW) radar; pseudo-random binary sequence (PRBS) generator; true single-phase-clock (TSPC) flip-flop

A 34 GHz CMOS VCO with Transformer Tail-Node Filter and TSPC Frequency Divider in 22 nm FDSOI - Engelmann, Andre; Probst, Florian; Hetterle, Philip; Weigel, Robert (2024 IEEE Radio and Wireless Week, RWW 2024 - 2024 IEEE 24th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, SiRF 2024, 2024)
This work proposes a compact, low-power CMOS voltage-controlled oscillator (VCO) with distributed transformer tail-node filter for phase noise reduction. The circuit is integrated into a 22 nm fully-depleted silicon-on-insulator (FDSOI) technology, offering high-performance n- and p-MOS transistors. Using a combination of SOI varactors and switched capacitors, a wide tuning range of 22.8%, covering 30.4 to 38.24 GHz, is reached while maintaining a phase noise below -97 dBc/Hz at a 1 MHz carrier offset. An area- and power-efficient true single-phase-clock (TSPC) frequency divider is implemented to ease the use of the VCO within a low-frequency PLL. The overall circuit consumes 9.4 mW supplied from a 0.8 V source and 170 370 m2 core area, including an output buffer and the divider. The circuit performance results in a corresponding FOM and FOMT of -178.3 and -185.3 dBc/Hz.
CRIS-Team Scopus Importer:2024-03-15
Keywords: CMOS; Cross-coupled VCO; FDSOI; frequency divider; low phase-noise; oscillator; signal generation; tail filter

A 3-Stacked 10.2 dBm OP1dB D-Band Power Amplifier in 22 nm FDSOI for 6G Communication - Huang, Tianzhu; Engelmann, Andre; Hetterle, Philip; Probst, Florian; Weigel, Robert (2023 Asia-Pacific Microwave Conference, 2023)
This paper proposes a high-linearity 3-stacked D-band power amplifier (PA) for 6G communication. The PA is fabricated in 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology and consists of four stages, including three driver stages. The capacitive neutralization approach is adopted in all stages for gain-boosting. Transistor stacking is applied in the output stage for high output power and linearity. The circuit achieves a peak power gain of 23.8 dB at 135 GHz with a 3-dB bandwidth of 16 GHz. A maximum measured output power of 13 dBm, an output referred 1-dB compression point OP1dB of 10.2 dBm, and a peak power-added efficiency (PAE) of 9.9% are attained, while occupying only 0.081 mm² of chip are
Keywords: CMOS; D-band; FDSOI; high linearity; mm-wave; power amplifier (PA); stacked amplifier; 6G

A Broadband 22 nm FDSOI D-Band Power Amplifier with Dynamic Back Gate Bias Gain-Linearization Achieving 9.6% PAE at 8.7 dBm OPldB and 3.7% at 6 dB Back-off - Engelmann, Andre; Scheller, Kai; Probst, Florian; Koch, Manuel; Weigel, Robert; Fischer, Georg (IEEE/MTT-S International Microwave Symposium - IMS 2024, 2024)
This work presents a high-efficiency four-stage D-band power amplifier (PA) in a 22 nm FDSOI technology. The PA incorporates a dynamic biasing scheme that utilizes the SOI transistor's back-gate terminal to optimize the DC power consumption of each stage based on the corresponding input envelope power level. This dynamic bias control significantly improves the linearity and efficiency in the linear and power compression range. The work describes the associated power detectors and the design of a stacked FET output stage used for output power enhancement. Low-k stacked transformers are employed as interstage matching elements to broaden the bandwidth. The PA achieves 24.5 dB gain, covering a 3-dB bandwidth of 36 GHz centered at 138 GHz. Saturated output power and OPldB of 10.8 dBm and 8.6 dBm at nominal supply voltage of 1.6/0.8V is reached while only occupying a core area of 0.045 mm 2 • Achieving 9.6% PAE at OPldB and 3.7% at 6-dB power back-off, the PA demonstrates significant improvement compared to reported D-band PAs in CMOS technolog

A Compact Energy-Saving D-Band Frequency Quadrupler with -1 dB Conversion Gain in 22 nm FDSOI - Engelmann, Andre; Probst, Florian; Hetterle, Philip; Weigel, Robert (2023 Asia-Pacific Microwave Conference (APMC), 2023)
This work presents a compact and energy-saving D-band frequency multiplier by 4 (quadrupler) integrated into an advanced 22 nm fully-depleted silicon-on-insulator (FDSOI) technology. The circuit consists of a multi-phase driven two-stage push-push doubler architecture achieving a conversion gain of -1 dB and covers a bandwidth of 23 GHz centered at 133 GHz. At 0.8 V supply voltage, the quadrupler attains a maximum output power of -3.4 dBm and an efficiency of 1.71% while consuming only 27 mW of DC power. A harmonic rejection greater than 26 dBc is reached over the entire bandwidth. The core cell of the circuit occupies a compact chip area of 325 × 250 μm2
CRIS-Team Scopus Importer:2024-12-16
Keywords: CMOS; D-band; FDSOI; frequency multiplier; MMIC; quadrupler; signal generation

A Continuously Adjustable True Time Delay for D-Band Timed Antenna Arrays - Koch, Manuel; Probst, Florian; Breun, Sascha; Weigel, Robert (2023 18th European Microwave Integrated Circuits Conference, EuMIC 2023, 2023)
This paper presents a fully integrated true time delay (TTD) circuit for beamforming applications based on the delay sum principle operating at a center frequency of 144 GHz with a 3 dB bandwidth of 26 GHz. It features a measured delay range of 1.75 ps whose resolution is only limited by the integrated digital-to-analog converter (DAC). A demonstrator has been manufactured in a 130 nm bipolar complementary metal-oxide-semiconductor (BiCMOS) technology, occupying 0.53 × 0.3mm 2 of chip area including serial peripheral interface (SPI), bandgap reference and four DAC
CRIS-Team Scopus Importer:2023-12-01
Keywords: BiCMOS integrated circuits; delay lines; phase shifters

A Dual-Channel 15 Gb/s PRBS Generator for a D-Band PMCW Radar Transmitter in 22 nm FDSOI - Probst, Florian; Engelmann, Andre; Koch, Manuel; Weigel, Robert (IEEE Wireless and Microwave Technology Conference, WAMICON 2023, 2023)
This work proposes an integrated baseband signal generator with multiple orthogonal outputs for phase-modulated continuous-wave (PMCW) radar. The circuit combines a linear-feedback shift register (LFSR), producing an m-sequence at a chip rate of 15 Gb/s, with a digitally implemented outer code (OC) generator. Different channels can be distinguished at the receiver through a slow-time modulation of the pseudo-random binary sequence (PRBS) with different Hadamard codes. The generator is integrated into a 1700×1300 μm² double-channel D-band radar transmitter on a 22nm fully-depleted silicon on insulator (FDSOI) technology, of which only 73×80 μm² are devoted to the baseband generator. A measurement setup is presented, where the transmitter’s D-band output signal is externally down-converted and sampled using a high-speed oscilloscope. In a series of offline digital signal processing (DSP) steps including correlation, accumulation and another correlation, the functionality of the proposed generator is demonstrated.<br
Keywords: Fully-depleted silicon on insulator (FDSOI); MIMO radar; phase-modulated continuous-wave (PMCW); joint radar-communication (RadCom); true single-phase-clock (TSPC)

A Low-Voltage Broadband D-Band BPSK Modulator for a PMCW Radar Transmitter in 22 nm FDSOI - Engelmann, Andre; Probst, Florian; Hetterle, Philip; Weigel, Robert; Dietz, Marco (Asia-Pacific Microwave Conference 2022 (APMC), 2022)
This work presents a broadband low-voltage binary-phase-shift-keying (BPSK) modulator operating in the D-band. The modulator is intended for a phase-modulated continuous-wave (PMCW) radar transmitter with a chip rate of up to 12.5 Gb/s and integrated into an advanced 22 nm fully-depleted silicon-on-insulator (FDSOI) technology. The circuit covers a bandwidth of 34 GHz at a carrier frequency of 140 GHz with a maximum conversion gain of 2.5 dB. A 1 dB output compression point of −7.2 dBm is reached while consuming 27 mW DC-Power at a supply voltage of only 0.8 V and a circuit core area of 0.051 sqm
Keywords: Binary-phase-shift-keying (BPSK) modulator; CMOS; D-band; FDSOI; MMIC; phase-modulated continuous-wave (PMCW) radar.

A Low Voltage Folded Gilbert Cell Mixer for 6G Communication Systems - Hetterle, Philip; Engelmann, Andre; Probst, Florian; Huang, Tianzhu; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2023)
This paper presents the design of a folded Gilbert cell D-band down-conversion mixer manufactured in a 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology. The mixer runs on a supply voltage of 800 mV and consumes a power of 28 mW. The device achieves a conversion gain of -7 dB while maintaining a broad bandwidth of 30 GH
Keywords: CMOS; D-band; FDSOI; Gilbert cell; down-conversion; low voltage; mixer; mm-wave; mobile communication; 6G

An Area Efficient Low-Power mmWave PRBS Generator in FDSOI - Probst, Florian; Engelmann, Andre; Dietz, Marco; Issakov, Vadim; Weigel, Robert (IEEE MTT-S International Microwave Symposium 2022, 2022)
This paper presents an area efficient, low-power pseudo-random binary sequence (PRBS) generator which is built of true single-phase-clock (TSPC) flip-flops that form a linear-feedback shift register (LFSR). Operating at a supply voltage of 0.88 V it can generate a 2¹¹-1 m-sequence with a maximum data rate of 33 Gb/s. The circuit is fabricated in a 22-nm fully depleted silicon on insulator (FDSOI) CMOS technology and occupies a core area of only 42 μm2. With a core power consumption of only 1.3 mW at the maximum data rate, it is well suited for its application as a baseband signal generator in a phase-modulated continuous-wave (PMCW) radar transmitter. The PRBS generator exhibits a figure of merit (FoM) of only 8 fJ/bit which represents an improvement by the factor of five compared to the current state of the art to the best of authors’ knowledge.<br

A Synchronized 35 GHz Divide-by-5 TSPC Flip-Flop Clock Divider in 22 nm FDSOI - Probst, Florian; Engelmann, Andre; Weigel, Robert (2023 Asia-Pacific Microwave Conference (APMC), 2023)

Bringing Portability to a New Level: A High-Sensitivity, Low-Power Monostatic CW Radar at 24 GHz - Peters, Sebastian; Horlbeck, Marie; Probst, Florian; Weigel, Robert (IEEE Microwave Magazine, 2022)
Radar technology offers unique advantages that distinguish it from conventional sensing technologies. Now, research on industrial sensor systems is rapidly increasing. Due to the massive integration of RF circuits in monolithic microwave integrated circuits in recent years, radar systems can be designed to be very compact, inexpensive, and at the same time, feature a low power consumption [1] , [2] . This development is also pushed by the digital transformation of production in various industries, commonly known as the fourth industrial revolution [3] , [4] . In industrial environments, radar technology offers various advantages over conventional sensors. The combination of high resolution, low power consumption, and operation in harsh environments makes radar sensors extremely attractive. Additionally, radar technology also stands out from other sensor technologies in the medical field. Radar systems can be used for simple presence monitoring or, due to the very high resolution, for gesture recognition or even for recording vital parameters. Minimal movements on the surface of the chest caused by respiration or heartbeat are strong enough to be detected by radar systems without contact [5] , [6] .<br

Design and Evaluation of a Low-Cost SAW Resonator Read-Out System at 2.4 GHz - Probst, Florian; Scheiner, Benedict; Michler, Fabian; Weigel, Robert; Lurz, Fabian (IEEE Transactions on Instrumentation and Measurement, 2022)

Design of a Low Voltage D-band LNA in 22 nm FDSOI - Hetterle, Philip; Engelmann, Andre; Probst, Florian; Weigel, Robert; Dietz, Marco (17th European Microwave Integrated Circuits Conference (EuMIC), 2022)
This paper presents a low voltage D-band Low Noise Amplifier (LNA) manufactured in a 22nm fully-depleted silicon-on-insulator FDSOI CMOS technology. The circuit consists of 4 differential stages. The first stage is optimized for minimal noise, while the other three are optimized to achieve maximum gain. Therefore, a capacitive neutralization technique is applied. Transmissionline-based matching networks are used to match the stages for a bandwidth of over 20 GHz. The measurement results show a gain of 17 dB while achieving a low noise figure of less than 8 dB at a supply voltage of only 0.8V.<br
Keywords: CMOS; D-band; FDSOI; LNA; mm-wave; mobile communication; 6G

Design of an E-TSPC Flip-flop for a 43 Gb/s PRBS Generator in 22 nm FDSOI - Probst, Florian; Weninger, Jonas; Engelmann, Andre; Issakov, Vadim; Weigel, Robert (18th European Microwave Integrated Circuits Conference (EuMIC), 2023)

Design of two Low DC-Power High-Efficiency D-Band Power Amplifiers in 22 nm FDSOI - Engelmann, Andre; Hetterle, Philip; Probst, Florian; Weigel, Robert; Dietz, Marco (17th European Microwave Integrated Circuits Conference (EuMIC), 2022)
This paper presents two low DC-power D-band power amplifiers (PAs) integrated into a 22nm fully-depleted silicon-on-insulator (FDSOI) technology. Both amplifiers use the capacitive neutralization technique for gain-boosting and stability enhancement. The design procedure for transformer-based (TB) and line-based (LB) matching networks and the advantages and disadvantages of both architectures are discussed. The PA implementation focuses on low DC-power consumption, high efficiency, and compact device realization. The fabricated TBand LB-PA show high maximum power-added-efficiency (PAE) of 9 and 8% consuming 46 and 52mW respectively at a supply voltage of only 0.8V. The saturated output powers Psat reach 6.8dBm and 6.5dBm while achieving small-signal gains of 24.2 and 23.4 dB with 3-dB-bandwidths of 23 and 26 GHz.<br
Keywords: Power amplifier (PA); D-Band; millimeter-wave; FDSOI; CMOS; phase-modulated continuous-wave (PMCW) radar

Low-Cost Six-Port for High-Volume Frequency Measurement Systems in the 2.4 GHz ISM-Band - Scheiner, Benedict; Probst, Florian; Michler, Fabian; Weigel, Robert; Kölpin, Alexander; Lurz, Fabian (IEEE Topical Conference on Wireless Sensors and Sensor Networks 2021, 2021)

Miniaturized Hybrid Frequency Reader for Contactless Measurement Scenarios Using Resonant Surface Acoustic Wave Sensors - Scheiner, Benedict; Probst, Florian; Michler, Fabian; Weigel, Robert; Kölpin, Alexander; Lurz, Fabian (Sensors, 2021)